2019
DOI: 10.14309/ajg.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of Diagnosis, Substantial Co-Occurrence, and Variable Treatment Patterns of Eosinophilic Gastritis, Gastroenteritis, and Colitis Based on 10-Year Data Across a Multicenter Consortium

Abstract: Objective: The literature related to eosinophilic gastritis (EG), gastroenteritis (EGE) and colitis (EC) is limited. We aimed to characterize rates of diagnosis, clinical features, and initial treatments of patients with EG, EGE, and EC. Methods: In this retrospective study, data were collected from six centers in the Consortium of Eosinophilic Gastrointestinal Researchers (CEGIR) from 2005-2016. We analyzed demographics, time trends in diagnosis, medical history, presenting symptoms, disease overlap, and init… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 34 publications
(45 reference statements)
1
103
0
Order By: Relevance
“…We previously reported that treatments such as corticosteroids or food elimination improved clinical, endoscopic, and histologic outcome measures [16]. The current study examined the impact of treatment on specific endoscopic and histologic findings.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We previously reported that treatments such as corticosteroids or food elimination improved clinical, endoscopic, and histologic outcome measures [16]. The current study examined the impact of treatment on specific endoscopic and histologic findings.…”
Section: Discussionmentioning
confidence: 93%
“…For this retrospective cohort study, centers from the Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR) were asked to participate and 6 centers (4 pediatric and 2 pediatric/adult) submitted subjects for enrollment [15]. Complete methodology and clinical characteristics of the study cohort were described previously [16]. Briefly, subjects were considered eligible for study inclusion if they were seen at enrolling sites between 2005 and 2016, had a clinical diagnosis of EG, EGE (EG and eosinophilic enteritis), and/or EC, and at least one endoscopy with biopsy demonstrating an increase in gastrointestinal eosinophils.…”
Section: Subject Selection and Areas Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophilic gastritis (EG) is one of the eosinophilic gastrointestinal disorders (EGIDs) characterized by marked eosinophil accumulation into the gastrointestinal tract, 1,2 with an estimated prevalence of about 6.3 patients per 100,000 subjects, which is likely increasing. 3,4 Although studies of eosinophilic esophagitis (EoE) have elucidated specific molecular, cellular, and immune mechanisms involved in its pathogenesis, 5 EG is more rare than EoE and thus less well understood, with few publications even addressing diagnostic criteria, genetics, biomarkers, or disease pathogenesis. Unlike in the esophagus, eosinophils normally reside in the gastric mucosa during homeostasis, 6,7 adding complexity to disease diagnosis and monitoring.…”
mentioning
confidence: 99%
“…The initial publication from this group reported that the rate of diagnosis of EGIDs has been increasing with a slight predominance of eosinophilic gastritis over that of enteritis and colitis [3]. More than a third of patients had eosinophilic inflammation outside of their primary disease location, most commonly within the esophagus.…”
mentioning
confidence: 99%